Pendidikan kesehatan mengenai pola hidup sehat pada penderita diabetes mellitus di Desa Sukajaya Lempasing Kabupaten Pesawaran - Furqoni, Prima Dian; Juliawan, Ladin; Sintia, Monica Bela Dwi; Natalia, Mutiara; Adhani, Neisa; Istawala, Anggun; Prayogo, Idfy Dwi; Fajrianti, Endah; Alam, Rama Rajasa Ferlanda; Saraswati, Ika (JOURNAL of Public Health Concerns, 2025)
Background: Diabetes mellitus (DM) is a chronic disease with a steadily increasing prevalence, particularly among the elderly. Data from the International Diabetes Federation (IDF) in 2022 showed that the number of diabetes sufferers in Indonesia reached 19.5 million people and is expected to increase to 28.6 million by 2045. Based on the 2018 Basic Health Research (Riskesdas), the prevalence of DM in those aged 15 years and older increased to 10.9%, with the highest rate in the 55–74 age group. In Pesawaran Regency, Lampung Province, the prevalence of DM reached 1.0%. Initial findings in Mutun Hamlet 7 indicate that most elderly people do not understand the importance of a healthy lifestyle in diabetes management. Health education is an effective strategy to increase awareness and independence in the elderly. Purpose: Increase knowledge and awareness of a healthy lifestyle through communicative educational activities tailored to the characteristics of elderly people with diabetes mellitus. Method: This activity was part of the Gerontology Nursing professional practice program held on Monday, June 2, 2025, in Dusun 7 Mutun. The methods used were lectures, discussions, and leaflet distribution. Ten elderly people with a history of diabetes participated. Results: This outreach activity had a positive impact on increasing the elderly's understanding of the importance of maintaining a balanced diet, engaging in light physical activity, and independently monitoring their blood sugar levels. Participants demonstrated active participation and stated that they gained new knowledge that they could apply in their daily lives. Conclusion: Health education has proven effective in increasing the knowledge of elderly people with diabetes about healthy lifestyles and encouraging them to become independent in managing their disease. Keywords: Diabetes mellitus; Elderly; Health education; Healthy lifestyle Pendahuluan: Diabetes mellitus (DM) merupakan penyakit kronis dengan prevalensi yang terus meningkat, terutama pada kelompok lanjut usia (lansia). Data International Diabetes Federation tahun 2022 menunjukkan bahwa jumlah penderita diabetes di Indonesia mencapai 19,5 juta orang dan diperkirakan meningkat menjadi 28,6 juta pada tahun 2045. Berdasarkan Riskesdas tahun 2018, prevalensi DM pada usia ≥15 tahun meningkat menjadi 10.9%, dengan angka tertinggi pada kelompok usia 55–74 tahun. Di Kabupaten Pesawaran, Provinsi Lampung, prevalensi DM mencapai 1.0%. Temuan awal di Dusun 7 Mutun menunjukkan sebagian besar lansia belum memahami pentingnya pola hidup sehat dalam pengelolaan diabetes. Pendidikan kesehatan menjadi strategi efektif dalam meningkatkan kesadaran dan kemandirian lansia. Tujuan: Meningkatkan pengetahuan dan kesadaran mengenai pola hidup sehat melalui kegiatan edukasi yang komunikatif dan sesuai karakteristik lansia penderita diabetes mellitus. Metode: Kegiatan ini merupakan bagian dari praktik profesi Ners Keperawatan Gerontik yang dilaksanakan pada Senin, 02 Juni 2025, di Dusun 7 Mutun. Metode yang digunakan adalah ceramah, diskusi, serta pembagian leaflet. Jumlah peserta sebanyak 10 orang lansia dengan riwayat DM. Hasil: Kegiatan penyuluhan ini memberikan dampak positif terhadap peningkatan pemahaman lansia mengenai pentingnya menjaga pola makan seimbang, melakukan aktivitas fisik ringan, serta memantau kadar gula darah secara mandiri. Peserta menunjukkan partisipasi aktif dan menyatakan memperoleh pengetahuan baru yang dapat diterapkan dalam kehidupan sehari-hari. Simpulan: Pendidikan kesehatan terbukti efektif dalam meningkatkan pengetahuan lansia penderita DM tentang pola hidup sehat dan mendorong lansia memiliki kemandirian dalam pengelolaan penyakit.